Grazing Exclusion Changed the Complexity and Keystone Species of Alpine Meadows on the Qinghai-Tibetan Plateau - Zhang, Yong; Gao, Qingzhu; Ganjurjav, Hasbagan; Dong, Shikui; Zheng, Qiuzhu; Ma, Yandan; Liang, Kemin (Frontiers in Ecology and Evolution, 2021)
Grazing exclusion is an effective approach to restore degraded grasslands. However, the effects of grazing exclusion on keystone species and the complexity of plant community were poorly investigated. Here, we conducted a field survey among different grazing exclusion durations, i.e., Grazing, grazing exclusion below 5 years, grazing exclusion with 5 years, grazing exclusion with 7 years, and grazing exclusion over 7 years, in alpine meadows on the central Qinghai-Tibetan Plateau (QTP). The complexity and keystone species of alpine meadows were analyzed by a network analysis. The results showed the following: (1) The species richness did not change, but aboveground biomass and the coverage of the plant community tended to increase with the extension of the grazing exclusion duration. (2) The soil nutrients, i.e., total nitrogen, total organic carbon, available nitrogen, and available potassium, remained stable, while the soil bulk density decreased under grazing exclusion conditions. (3) There was a hump-shaped change of the complexity (i.e., average connectivity and average clustering coefficient) of the plant community along with the extension of the grazing exclusion duration. Moreover, the keystone species were different among the grazing exclusion treatments. Based on the complexity of the plant community and the changes of keystone species, the optimum duration of grazing exclusion for alpine meadows should be between 5 and 7 years. Our results suggest that besides the productivity, the change of the complexity and keystone species of plant community should be considered when grazing exclusion is adopted to restore the degraded alpine meadows.